Innovative opportunities for gene editing technology in crop breeding: from the perspective of literature analysis - Zhang, Hui; Yao, Ru; Jia, Qian; Qi, Shijie; He, Ying; Zhao, Jingjuan; Chuan, Limin (Frontiers in Plant Science, 2025)
Gene editing technology is a revolutionary biotechnology that has shown great potential and advantages in crop breeding. Current research has proposed many technical methods and design schemes for gene editing technology in crop breeding. However, summarization and analysis are often based on the research and application of a certain technology, lacking a literature content mining perspective to summarize and analyze the application of gene editing and other technologies in crop breeding. At the same time, there is insufficient identification of future research and innovation opportunities of gene editing technology in crop breeding. This study utilized natural language processing, deep learning, and generative topographic mapping (GTM) to conduct an in-depth analysis of the literature on gene editing technology in crop breeding from the perspective of literature mining. Key technical terms in this field were identified, a literature technical map was constructed, technical blank points were identified, and innovative opportunities for blank technology combinations were analyzed. The results showed that from the literature data from 2020 to 2024, 13 technology combinations were identified. These technical contents cover the multi-technology combination strategy of molecular genetic research, the core technology of gene function research in molecular genetics of biotic and abiotic stresses, the technical means of analyzing the molecular mechanisms of stress resistance, the technical scheme of genetic improvement, etc., which provide support for revealing the potential technological innovation opportunities of gene editing technology in the field of crop breeding. This study can scientifically, objectively, and efficiently identify technological innovation opportunities from the literature. Based on the research results, future research should carry out experimental research and application exploration so as to support the application and technological innovation of gene editing technology in crop breeding.